Peran Ombudsman dalam Efektivitas Penyelesaian Sengketa Maladministrasi Pelayanan Publik: Penelitian - Indra Perwira Semar; Ismail; Dhoni Martien (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The establishment of the Ombudsman Institution aims to change the paradigm of public service that tends to be long-winded and prioritizes certain parties to a public service that serves all levels of society and can satisfy the public as consumers. This institution is expected to be a solution to the many public dissatisfaction with the implementation of public services that often cause material and immaterial losses for the community. The public who experience disputes regarding public service maladministration can report these to the Ombudsman of the Republic of Indonesia. Research on the role of the Ombudsman in the effectiveness of resolving public service maladministration disputes is important to determine whether equality and justice for all people have been achieved. The purpose of this study is to determine the role of the Ombudsman in effectively resolving public service maladministration disputes. The research method used in this study is normative legal research. In this study, it was found that the effectiveness of the Ombudsman's role in resolving maladministration disputes was quite good and effective, but there were still many people who were not aware of the existence of this institution and also the regulations were still overlapping so that the results of the Ombudsman were not strong enough to be binding.